Urtikaria - Warning, Albrecht; Gupta, Hedwig; Sauer, Helmut (Zeitschrift für Komplementärmedizin, 2019)
3 Fachleute – 3 Behandlungsmethoden
Keywords: Urtikaria; Urtica dioica – Öldispersionsbad; Ayurveda; Eigenblutbehandlung